The Effectiveness of Individual Counseling Services with a Reality Counseling Approach to Increase Self-Acceptance in Orphanage Children - Surbakti, Fitri Br; Putri Harahap, Ade Chita (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This study aims to test the effectiveness of individual counseling services with a reality counseling approach in increasing self-acceptance in children in orphanages. The study used an experimental method with a Pre-Experiment model and The One Group Pretest and post-test design. The population in this study was all 378 orphanage children, and the subjects used in the study were five orphanage children using a purposive random sampling technique. Self-acceptance was measured using a Likert scale before and after the counseling intervention. The primary data source used in the study was the test results from 5 informants (children in orphanages), and secondary data using sources relevant to the study. Data collection techniques used observation, tests, and documentation. Data analysis was carried out using the Wilcoxon Signed Rank Test to test for significant differences between the pretest and posttest. The results showed that individual counseling services with a reality counseling approach significantly increased children's self-acceptance. Through a series of counseling sessions, children learn to face the realities of their lives more positively and adaptively, develop higher self-awareness, and build effective coping skills. These findings provide important contributions to the fields of psychology and counseling, especially in helping children in orphanages develop self-acceptance and face life challenges more optimistically. Although this study has limitations, such as a small sample size, the results provide a strong basis for similar interventions in the future.